O pinhão como foco de uma sequência de ensino investigativa em ciências para os anos iniciais do ensino fundamental - Santos, Cíntia Daniele Silva dos (2023)
Natural Sciences are part of the students' daily lives, that is, their reality. Relating everyday events to the content to be worked on enables the development of meaningful learning, as these become meaningful and relevant in the lives of students. At school, as the contents of Science have been worked on, many times, they do not meet the needs of the student. Teaching by investigation presents itself as a possible approach capable of bringing favorable results to the teaching/learning process, making it attractive and engaging, stimulating the construction of knowledge by the student and his autonomy. This dissertation aims to investigate how an investigative teaching sequence, based on the central theme of pinion, can contribute to the scientific literacy of students in the Early Years of Elementary School. The research had a qualitative approach and the procedure adopted was the case study. It was developed with 20 students from the 3rd and 4th years of Elementary School, from a school in the central region of Rio Grande do Sul – Brazil. A Sequence of Teaching by Investigation was proposed, which had as its starting point the June Festivals, more specifically the pinion, being organized in 5 modules. Data collection was carried out through a Logbook, descriptive sheets, material, images, transcription of audios and videos. The evaluation was carried out based on the analysis of the collected data. The work carried out fulfilled the necessary steps for scientific investigation, promoted the development of Scientific Literacy and provided the construction of meaningful learning. Teaching by investigation in Science provided students not only with the contact with the syllabus necessary for the educational stage in which they are inserted, but mainly, the construction and apprehension of knowledge related to them. Thus, when we promote teaching by investigation, we contribute to the formation of a critical, questioning, aware and active subject in society. We emphasize that this is not an end, but a beginning, the beginning of a different way of working in Science – scientific investigation. A means of bringing the contents of this discipline closer to the students' daily lives, showing that they are also there. It is a contribution, indicating that it is possible to carry out an interdisciplinary and meaningful work for students. It is also the beginning of these students' Scientific Literacy, a first stage of many that we hope will follow and that will contribute to evolutions in the present and to the construction of a better future.